2008
DOI: 10.1111/j.1469-8749.2008.03119.x
|View full text |Cite
|
Sign up to set email alerts
|

Do patients with congenital hemiparesis and ipsilateral corticospinal projections respond differently to constraint‐induced movement therapy?

Abstract: This study investigates whether the type of corticospinal reorganization (identified by transcranial magnetic stimulation) influences the efficacy of constraint-induced movement therapy (CIMT). Nine patients (five males, four females; mean age 16y [SD 6y 5mo], range 11-30y) controlling their paretic hand via ipsilateral corticospinal projections from the contralesional hemisphere and seven patients (three males, four females; mean age 17y [SD 7y], range 10-30y) with preserved crossed corticospinal projections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
136
9
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 140 publications
(157 citation statements)
references
References 31 publications
(46 reference statements)
8
136
9
3
Order By: Relevance
“…fMRI studies of cerebral activation of children with hemiplegia showed a shift in laterality from the ipsilateral to contralateral hemisphere after CIMT therapy in association with improved function [Eliasson et al, 2005]. Kuhnke et al [2008] found that children with congenital hemiparesis and preserved contralateral corticospinal tracts from the damaged hemisphere respond differentially to CIMT than children with only ipsilateral responses to TMS. Both groups respond to CIMT with improved function but only those with contralateral corticospinal tracts have improvement in speed of movement.…”
Section: Plasticity In Children With Cerebral Palsymentioning
confidence: 99%
“…fMRI studies of cerebral activation of children with hemiplegia showed a shift in laterality from the ipsilateral to contralateral hemisphere after CIMT therapy in association with improved function [Eliasson et al, 2005]. Kuhnke et al [2008] found that children with congenital hemiparesis and preserved contralateral corticospinal tracts from the damaged hemisphere respond differentially to CIMT than children with only ipsilateral responses to TMS. Both groups respond to CIMT with improved function but only those with contralateral corticospinal tracts have improvement in speed of movement.…”
Section: Plasticity In Children With Cerebral Palsymentioning
confidence: 99%
“…Gordon et al, 2006], while others have extended treatment to 2 months [Eliasson et al, 2005]. In addition, some therapy sessions have been provided on an individual basis [Crocker et al, 1997;DeLuca et al, 2003;Karman et al, 2003;Miller and Hale, 2005;Dickerson and Brown, 2007;Naylor and Bower, 2005;Cope et al, 2008;Fergus et al, 2008;Martin et al, 2008] while others are group based [Eliasson et al, 2003;Gordon et al, 2006;Charles and Gordon, 2007], or have combined both group and individual treatment sessions [Kuhnke et al, 2008]. Treatment environments have included home, clinic, and camp models, while interventionists have also varied from study to study including mostly Occupational and Physical Therapists but also trained caregivers, aides, and teachers.…”
Section: Application Of Cimt With Children With Hemiparesismentioning
confidence: 99%
“…One recent study [Kuhnke et al, 2008] noted that prenatal disruption of corticospinal projections may result in two patterns of cortical adaptation: persistence of normally transient ipsilateral projections, which then gain some control over the hemiparetic limb, or preservation of the more typical crossed projection pattern in weakened form. They determined type of corticospinal organization in adolescents and adults aged 10-30 with congenital hemiparesis through TMS.…”
Section: Summary; Issues For Future Researchmentioning
confidence: 99%
“…2 In contrast to us, they did not study prototypical samples of patients with distinct types of cerebral lesions and corticospinal organization, but investigated a typical clinical sample of 16 children and adolescents chosen by their eligibility for CIMT according to clinical characteristics; both transcranial magnetic stimulation and MRI data were available for 11 participants. This sample included patients with contralateral, ipsilateral, and 'mixed type' cortico-spinal projections; underlying lesions comprised maldevelopments, white matter lesions and ischemic cortico-subcortical infarcts.…”
mentioning
confidence: 98%
“…Two aspects of mastery motivation are persistence (the duration of task-directed behavior) and mastery pleasure (positive affect during or immediately after task-directed behavior). Children's mastery motivation is a force that energizes, directs, and sustains goal-directed behavior 2 and is a predictor of later functioning. 3 For children with developmental disabilities, mastery motivation is also a predictor of later performance of daily activities and academic achievement.…”
mentioning
confidence: 99%